PENGARUH GAYA MENGAJAR GURU DAN DISIPLIN MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SISWA IPS KELAS XI SMA YLPI PEKANBARU - Annisa, Nur; Caska, Caska; Kartikowati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The number of students who do not achieve the minimum standard score on the learning outcomes is an obstacle for the Economics teachers of XI class at SMA YLPI Pekanbaru. The student’s low achievement are influenced by several factors like the teaching styles and discipline by the teacher in intructional process. Teachers are required to choose attractive teaching style, high discipline attitude and have an enthusiasm to study in order to get a better learning achievement. The purpose of this study determine the effect of teachers teaching style and teachers disciplin in teaching on the student’s learning achievement with the subject of Economics students of XI class SMA YLPI Pekanbaru. This research used quantitative descriptive method and population research is all economic students of XI class wich consist of 41 students. Saturated sampling is conducted in the sampling technique wich all the members of the population are used the samples. Morever, questionnaires are used for data collection techniques. Data analysis techniques used descriptive statistics, linear regression analysis and coefficient of determination (R2) with the help of SPSS 16.0 version. The results of study indicate the teaching style and teachers discipline in teaching influenced the student learning achievement on the determination R2 of 64.6%. after this research, the teacher expected create a pleasing atmosphere in teaching learning process and improvement of discipline and enthusiasm in teaching as an support for the students success in learning.Keywords: Teacher teaching style, disciplin of teachers teaching, student learning achievement